The doctrine of the Responsibility to Protect: Concept and scope of application - Ola, Alkayid; Ossama, Almanasa; Almazaidah, Ismail (Research Journal in Advanced Humanities, 2025)
This study examines the doctrine of the Responsibility to Protect (R2P) as a transformative framework within contemporary international law, particularly in contexts marked by mass atrocity crimes such as genocide, ethnic cleansing, war crimes, and crimes against humanity. The research aims to examine the conceptual foundations of R2P, its legal and normative pillars, mechanisms of implementation, and the evolving relationship between national sovereignty and international responsibility. It employs a qualitative legal analysis based on the study, which investigates primary sources including UN documents, international conventions, and judicial precedents, as well as secondary literature in Arabic and English. It critically analyzes the conditions under which R2P may be activated, including the occurrence of grave human rights violations and the inability or unwillingness of states to provide protection. The findings reveal that R2P has shifted the paradigm of sovereignty from exclusive control to functional responsibility. While the doctrine has gained global legitimacy, its practical implementation faces persistent challenges such as politicization, resource limitations, and inconsistent application. The study concludes that effective operationalization of R2P requires institutional reform within the UN system, early warning mechanisms, and a balanced approach to its three pillars: prevention, response, and rebuilding. The paper offers actionable recommendations to enhance both national and international capacities in fulfilling the doctrine’s protective mandate.